2019
DOI: 10.1029/2018jb016925
|View full text |Cite
|
Sign up to set email alerts
|

Long‐Lasting Evolution of Layer 2A in the Western South Atlantic: Evidence for Low‐Temperature Hydrothermal Circulation in Old Oceanic Crust

Abstract: Previous seismic studies suggest that hydrothermal processes are active only within young oceanic crust (<10–16 Ma). However, differences between measured and predicted heat flow at the ocean floor indicate that hydrothermal fluids may be transporting heat advectively in crust up to ages of 65 Ma. We report on seismic velocities of 0–71 Ma slow to intermediate spreading rate upper crust in the western South Atlantic. Thirteen high‐resolution 2‐D velocity models were built using traveltime tomography on downwar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
100
2

Year Published

2019
2019
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(116 citation statements)
references
References 117 publications
(211 reference statements)
14
100
2
Order By: Relevance
“…Our layer 2A thickness estimates contain significant variability, which introduces a broad distribution and substantial scatter when examining trends. The values of layer 2A thickness reported by Kardell et al () contain a similar standard deviation as ours, but their results do not include the rapid variation we observe (Figures and ). We believe two primary contributing factors to be predominantly responsible for the scatter we observe in our thickness values.…”
Section: Discussionsupporting
confidence: 62%
See 4 more Smart Citations
“…Our layer 2A thickness estimates contain significant variability, which introduces a broad distribution and substantial scatter when examining trends. The values of layer 2A thickness reported by Kardell et al () contain a similar standard deviation as ours, but their results do not include the rapid variation we observe (Figures and ). We believe two primary contributing factors to be predominantly responsible for the scatter we observe in our thickness values.…”
Section: Discussionsupporting
confidence: 62%
“…Furthermore, our thickness range roughly brackets those of previous studies, indicating our values are reasonable. Kardell et al () found slightly different layer 2A thickness values along the CREST transect where they obtained velocity models. We believe the difference is a product of both data and methods.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations